Characterization of GMB-1, a novel metallo-β-lactamase (MBL) found in three different Enterobacterales species. (8th March 2022) - Schauer, Jennifer; Gatermann, Sören G; Eisfeld, Jessica; Hans, Jörg Berthold; Ziesing, Stefan; Schlüter, Dirk; Pfennigwerth, Niels
Abstract: Objectives: To identify novel carbapenem resistance mechanisms and their potential to spread among clinical isolates. Methods: Four clinical isolates of Citrobacter freundii, Serratia marcescens and Raoultella planticola ( n = 2) from one hospital in Central Germany were sent to the German National Reference Centre for Multidrug-resistant Gram-negative Bacteria for carbapenemase detection. Phenotypic tests indicated the presence of a metallo-β-lactamase (MBL), but PCR for various MBL genes could not identify any. Using WGS data, a putative bla gene was identified. Its carbapenemase activity was verified by heterologous expression in an Escherichia coli cloning strain, with subsequent MIC determination by broth microdilution, as well as by in vitro hydrolysis assays using purified enzyme. Results: WGS indicated the presence of a putative β-lactamase with 48% amino acid identity to the subclass B1 MBL SPM-1. MIC studies confirmed that the novel enzyme formed a functional MBL, which was therefore designated as GMB-1 (German MBL). In vitro hydrolysis assays showed a lack of activity not only against aztreonam but also against ertapenem. WGS revealed that in all three species the bla GMB-1 gene was located on the chromosome as part of a genetic island with multiple ISs. Conclusions: The finding of GMB-1 once again shows that novel carbapenemases continue to emerge and make their way into clinically relevant species. The occurrence of GMB-1 in three different species demonstrates the extraordinary mobility of such genetic islands and their potential to spread carbapenemase genes into diverse genetic environments.